Prospective multicentre PCR-based Aspergillus DNA screening in high-risk patients with and without primary antifungal mould prophylaxis. (January 2016) - Springer, J.; Lackner, M.; Nachbaur, D.; Girschikofsky, M.; Risslegger, B.; Mutschlechner, W.; Fritz, J.; Heinz, W.J.; Einsele, H.; Ullmann, A.J.; Löffler, J.; Lass-Flörl, C.
Abstract: Invasive aspergillosis (IA) is associated with significant morbidity and mortality, and, among other factors, this is due to a delay in diagnosis performed with conventional techniques. A prospective, multicentre study was conducted to evaluate the efficacy of Aspergillus DNA screening in the early diagnosis of IA. Patients undergoing haematopoietic stem cell transplantation or chemotherapy for acute leukaemia were enrolled for biomarker screening. Three centres applied the same protocol for in-house PCR, which was compliant with the European Aspergillus PCR Initiative recommendations, to guarantee the highest diagnostic standards. Two thousand one hundred and twenty-eight sera from 213 patients were investigated and stratified according to the revised European Organization for the Research and Treatment of Cancer/Mycoses Study Group criteria for invasive fungal disease. The incidence rates of probable and possible IA were 18% and 38%, respectively. The sensitivity, specificity and positive predictive value (PPV) of PCR were superior in antifungal drug-naive patients, being 71.4%, 92.3%, and 62.5%, respectively. The last of these key performance indicators (PPV) was moderate in patients receiving primary prophylaxis, at 5.4%. Negative predictive values for both strategies applied were 100% with and 98.3% without antifungal mould prophylaxis. PCR has the potential to play a decisive role in the diagnosis and management of Aspergillus infections in centres not applying primary antifungal mould prophylaxis.